A SYNERGISTIC ABSORPTION AND PLASMONIC EFFECT OF SiO2@Au@TiO2 IN TiO2 PHOTOANODE FOR DYE-SENSITIZED SOLAR CELLS - Matius Nata Pakpahan; Aldi Hartanto; Yonatan Davidson Gultom; Nur Fadhilah; Doty Dewi Risanti (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2021)
A SYNERGISTIC ABSORPTION AND PLASMONIC EFFECT OF SiO2@Au@TiO2 IN A TiO2 PHOTOANODE FOR DYE-SENSITIZED SOLAR CELLS. A method for increasing the visible-light harvesting of a TiO2 anatase photoanode in dye-sensitized solar cells by incorporating plasmonic nanostructures was developed. Sidoarjo mud as the SiO2 source was used to successfully synthesized core/multishell SiO2@Au@TiO2, with varying amounts of Au (60, 90, and 120 mL). In addition, the core/multishell fractions in TiO2 paste were varied, i.e., 0.5%, 1%, and 5%. The UV–Vis spectrum shows that a more ripple spectrum at higher wavelengths is obtained with increasing Au content, as suggested by the presence of large Au nanoparticles; however, a similar value of efficiency is observed for all sample variations studied compared to a pure TiO2 photoanode. The incident photon-to-current efficiency reveals that all photoanodes containing the core/multishell SiO2@Au@TiO2 studied show somewhat broader and enhanced spectra for all studied wavelengths compared to the pure TiO2 photoanode, resulting from the synergistic effect between plasmonic nanostructures and the presence of silica that boost the absorption to higher wavelengths.